Analysis of the annual cycle of the precipitable water vapour over Spain from 10‐year homogenized series of GPS data. (22nd May 2013) - Ortiz de Galisteo, J. P.; Bennouna, Y.; Toledano, C.; Cachorro, V.; Romero, P.; Andrés, M. I.; Torres, B.
Abstract This study reports the characteristics of precipitable water vapour (PWV) at ten sites over Spain from 10 yr of hourly data from ground‐based global positioning system (GPS) receivers. The PWV data series from the GPS sites was inhomogeneous owing to a change in calibration procedure for variations of the antenna phase centre in November 2006. Radiosonde data therefore were used to homogenize the GPS data series and to assess the quality of the GPS measurements. The annual average value of PWV ranges from 14.5 to 20.0 mm, with an average of 18.3 ± 1.9 mm for Spain as a whole. The highest values are registered at sites on the coast, especially on the Mediterranean coast, and lowest values were at inland sites. The PWV presents a clear annual cycle, with a minimum in winter and maximum at the end of the summer. However, the southwestern sites present a relative minimum in July. This minimum seems to be related with the presence of drier air masses in the atmospheric layers between 1 and 4 km altitude. The amplitude of the cycle ranges from 8.9 to 18.7 mm. The largest amplitudes are found at the Mediterranean coastal sites (approximately 15–19 mm) and the lowest found at inland sites (approximately 9–10 mm). A harmonic analysis of the annual cycle showed that the 12 month harmonic explains, on average, over 96% of the variance. The average annual regime of PWV followed the cycle of the temperature, except for the relative minimum of PWV in July at the southwestern sites.